Investigation of Nitrogen Fixation Efficiency in Diverse Alfalfa Varieties Utilizing Sinorhizobium meliloti LL2 - Yilin Han; Wenjuan Kang; Shangli Shi; Jian Guan; Yuanyuan Du; Fuqiang He; Baofu Lu; Ming Wang (Agronomy, 2024)
To investigate the precise and efficient symbiosis between Sinorhizobium meliloti LL2 and different alfalfa varieties, we conducted experiments using eight alfalfa varieties along with the S. meliloti LL2. Our objective was to identify highly effective symbiotic combinations by analyzing differences in nodulation, nitrogen fixation, and biomass accumulation. The results revealed that Gannong NO.9 had higher values for single effective root nodule weight (1.30 mg) and the number of infected cells in root nodules (2795) compared to other varieties (p < 0.05). Additionally, Gannong NO.9 exhibited the highest nitrogenase activity (0.91 μmol·g−1·h−1), nitrogen fixation percentage (67.16%), and amount of nitrogen fixation (18.80 mg/pot). Moreover, there was a significant 26.50% increase in aboveground tissue nitrogen accumulation compared to the control check (CK) (p < 0.05). Furthermore, underground tissue showed excellent values for nitrogen accumulation (35.68 mg/plant) and crude protein content (17.75%) when compared with other treatments. The growth of plants was demonstrated by the combined impact of nodulation and nitrogen fixation. The distribution of biomass after nitrogen fixation was compared to the control group (p < 0.05) to investigate accumulation. The eight combinations of symbiotic nitrogen fixation (SNF) were classified into six distinct types based on their significantly different biomass growth rates compared to CK. ① Aboveground accumulation type: Gannong NO.9 (there was a 24.31% increase in aboveground dry weight); ② aboveground and underground accumulation type: Qingshui (the aboveground dry weight increased by 135.94%, while the underground dry weight grew by 35.26%); ③ aboveground accumulation, underground depletion type: Gannong NO.5 ( ); ④ zero-growth type (there was no significant difference in dry weights, both above and below ground, compared to CK): WL168HQ, WL319HQ and Longzhong; ⑤ aboveground and underground depletion type: WL298HQ (the aboveground dry weight decreased by 29.29%, while the underground dry weight decreased by 20.23%); ⑥ underground depletion type: Gannong NO.3 (the underground dry weight showed a decrease of 34.49%); no type with aboveground consumption and underground accumulation was found. The study clarified the optimal combination of LL2 and Gannong NO.9, finding that biomass accumulation after symbiotic nitrogen fixation is variety-dependent.